The accuracy of reading speed measurement by stopwatch versus measurement with an automated computer program (rad‐rd©) - Radner, Wolfgang; Diendorfer, Gabriela; Kainrath, Bettina; Kollmitzer, Christian (Acta ophthalmologica (Oxford, England), 2017)
Purpose To compare the reading time and reading speed measurements obtained with a stopwatch with those of an automated computer program for measuring reading speed and acuity (rad‐rd©; patent: AT 504635B1/10‐2006). Methods The rad‐rd© was used (in conjunction with a PC and microphone) for the computer‐based measurements. In rotation, each of four examiners took a turn reading the 12 sentences from one of the four RADNER Reading Charts to three other examiners, who served as stoppers. The stoppers simultaneously measured the reading time with a stopwatch while a fifth investigator used the rad‐rd© to obtain computerized measurements. The stopwatch measurements were then statistically compared with the rad‐rd© measurements. Results The mean reading time obtained with the stopwatch measurements was 4.34 ± 0.57 seconds (196.21 ± 21.79 wpm), versus 4.44 ± 0.59 seconds (192.24 ± 22.20 wpm) by computer measurement (r = 0.84). Of the 144 stopwatch measurements, 97 (67.36%) were shorter, and 47 (32.64%) were equal to (n = 5) or longer than the computer measurements. The mean difference for the shorter measurements was −0.17 ± 0.1 seconds (3.91% of the mean reading time), and the mean difference for the longer measurements was 0.11 ± 0.1 seconds (2.53% of the mean reading time). Most differences ranged from −0.1 to 0.1 seconds (42.36%). The results did not differ significantly among the four stoppers. Conclusion The rad‐rd© is an accurate, automated computer program for measuring reading time. Stopwatch measurements, although subject to inaccuracy from several sources, remain a reliable and simple method for analysis of reading performance.